IMPLEMENTASI AKAD IJARAH BANK BNI SYARIAH CABANG PALU - Murniati Ruslan (Fakultas Syariah Institut Agama Islam Negeri Palu, 2019)
BNI Syariah is one of Indonesia's national sharia banks. In its operations, BNI Syariah implements several contracts, namely the Mudharabah Contract, the Wadiah Contract, and the Ijarah Contract. This study is focused on the discussion of the Ijarah Contract by taking BNI Syariah Branch Palu, Central Sulawesi as the research object. Islamic banking has good prospects. This is supported by two factors, they are the population which is predominantly Muslim and the strong support of the Government. But at the same time, there are number of challenges faced by this type of banking. The aspects of funding and the quality of Human Resources (HR) are two elements that are often referred to the serious problems faced by Islamic banking, especially when compared to conventional banking. Another factor is that Islamic banking has not had a clear business model scheme yet. Moreover, Islamic banking products are still not fully understood by a larger public. In other words, citizens who truly understand the principles and products of Islamic banking are still very limited. In relation to the operations of the BNI Syariah Bank Branch Palu, there are two segments that are practiced in the bank intermediation. Those two segments are the consumptive segment and the productive segment. Both of these segments face the same problem in their implementation, it is socialization. This study found that there was a correlation between the lack of socialization and the low interest of the people in Palu regarding the Ijarah product. In other words, lack of socialization has caused BNI Syariah Branch Palu products to be widely unknown to the public.